Natural resources and environment: Governance for nature-positive food systems - Meinzen-Dick, Ruth S.; Ringler, Claudia; Zhang, Wei; Arndt, Channing (International Food Policy Research Institute, 2021)
Rethinking food system policies in terms of “eco-agro-food systems” can help to foster an integrated approach that will maintain and restore vital ecosystem services and reduce the likelihood of future shocks to our food and health systems. KEY MESSAGES - COVID-19 has brought home the necessity of better integration of natural resources and ecosystems with human food systems to increase the resilience, health, and sustainability of food systems. - Environmental degradation and climate change, in which food systems play a prominent role, are likely to increase the frequency and severity of natural disasters and may increase future pandemics, both causing shocks to food and health systems. - Common agricultural practices often degrade ecosystem services such as soil fertility and natural pest control, and can contribute to greater reliance on external inputs with potential for further damage. - Poor people are heavily dependent on natural resources for their livelihoods and are often most severely affected by environmental shocks and resource depletion. - The vicious cycle of unsustainable resource use and environmental degradation must be replaced with a virtuous cycle of healthier food and ecosystems using approaches that improve outcomes for humans and nature. - National laws and institutions, plus local formal and informal institutions and norms about respecting (or exploiting) nature, shape how people interact with the natural resource base and thus the outcomes for food and natural systems.